IMPLEMENTASI KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA DI KABUPATEN SUMEDANG - Anne Friday Safaria; Sri Sumiati; Tintin Karwati (JRPA - Journal of Regional Public Administration, 2020)
This research aims to see implementations of street vendor relocation policy, constraining factorimplementations of street vendor relocation policy, and efforts made to addreses implementation of streetvendor relocation policy in Dinas Koperasi, UKM, Perdagangan dan Perindustrian Sumedang District.This research methode uses qualitative descriptive (Naturalistic Setting). The sampling was troughliterature and observation (interview and documentation). The sampling in this research using purposivesampling which mean consist of 3 people. While data processing procedures using data analytical modelMiles and Huberman consisting of data reduction, data presentation, and verification. The result of thisresearch conclude that implementations of street vendor relocation policy Dinas Koperasi, UKM,Perdagangan dan Perindustrian Sumedang District has been going well but not maximally. It’sindicated by phenomena of (1) there’s too much illegal street vendor (2) too much street vendor insidewalk (3) low awareness against government regulations (4) lack of obdience to government policies.The suggestions for this research is do more socialization with street vendor, cooperate with tenantrelation, giving specification tasks, and carry out stricted supervision which mean the goals of policy canbe achived.